A social network perspective on virtual organisations: social structure as enabler and barrier. (13th November 2007) - Pedersen, Jens Dahl
Classic perspectives on virtual organisations are based on a technical systems understanding and thus offer an undersocialised perspective on the action and performance of these organisations. This article examines three classic perspectives and introduces the social network perspective for the analysis and management of virtual organisations. It particularly examines how the social structure of interorganisational relationships may enable and constrain the formation of and cooperation in virtual organisations. The article hereby aims to propose a more balanced sociotechnical understanding of virtual organisations. For the study of virtual organisations, the social network perspective introduces concepts describing the quality and structure of interorganisational relationships, and the conceptualisation of social capital and trust. The social network perspective suggests that managers focus on relationship management.